RATIONALE FOR THE TECHNICS OF JEJUNO- AND COLOSTOMIES APPLICATION FOR TREATMENT PURPOSES IN PATIENTS WITH ACUTE INTESTINAL OBSTRUCTION AND PERITONITIS - Vladimir I. Belokonev; Andrey G. Zhitlov; Andrey I. Gritsaenko; Yuriy I. Erdeli (Креативная хирургия и онкология)
Introduction. The following article contains the consideration of issues, related to rationale for the technics of jejuno- and colostomies’ application for treatment purposes in patients with acute intestinal obstruction and peritonitis. Currently such methods as Brooke’s ileostomy, double-barrel stoma and Maydl stoma are used in case intestinal stoma application is indicated. However, these types of operations have several disadvantages, resulting in stoma malfunction, exteriorized intestine necrosis and incarceration in a paracolostomal canal. These complications, among others, affect the treatment outcomes and mortality rate in acute intestinal obstruction and peritonitis. Materials and methods. The authors have proposed and applied new variants of trunk-shaped jejuno-, ileo- and colostomy and a new technology of stoma formation on an intestine, fixed in the abdominal cavity. Results. A comparative analysis of applied stomas has revealed a bigger correspondence of trunk-shaped stomas to such technical requirements as simplicity, reliability, efficacy and safety, in comparison with other treatment options, which results in treatment outcomes improvement and favorable prognosis in this complicated category of patients.